Performance evaluation of Indonesia's large and medium-sized industries using Data Envelopment Analysis method - Putri, Erni Puspanantasari; Aduldaecha, Sukon; Putra, Bonifacius Raditya Sri Pramana; Puteri, Agatha Hannabel Avnanta (OPSI, 2024)
Performance evaluation is essential for an industry's ability to operate successfully. Efficiency management is becoming crucial and important to enhancing the sustainability of the industry. The industry needs to measure its performance for the following reasons: (i) develop the economy and its operation efficiency in a sustainable way; (ii) supply data for decision-making units (DMUs); and (iii) optimize output using the fewest resources. Performance measurement indicators relate to the performance of the industry itself, such as: added value/cost of production factors, indirect taxes, number of workers, input costs, number of companies, added value/market prices, and production index. The purpose of this research is to measure the performance of large and medium-sized industries (LMIs) in Indonesia. LMIs have a strategic role as the main engine and driver of the economy. Measuring LMI performance is very necessary so that LMI can grow and develop sustainably. Data envelopment analysis (DEA) is a method for measuring performance. DEA is a non-parametric linear programming technique and used to determine comparisons between DMUs with different inputs and outputs. The research results indicate that there are three DMU classification categories, namely: Category 1 (ES = 1), Category 2 (ES = 0.9986-0.9998), and Category 3 (ES = 0.9971-0.9974). The percentages for each category are 50%, 37.5%, and 12.5%.